In vivo animal studies help achieve international consensus on standards and guidelines for health risk estimates for chronic exposure to low levels of tritium in drinking water. (27th August 2018) - Guéguen, Yann; Priest, Nicholas D.; Dublineau, Isabelle; Bannister, Laura; Benderitter, Marc; Durand, Christelle; Ebrahimian, Teni G.; Grégoire, Eric; Grison, Stéphane; Ibanez, Chrystelle; Legendre, Audrey; Lestaevel, Philippe; et al.
Abstract : Existing and future nuclear fusion technologies involve the production and use of large quantities of tritium, a highly volatile, but low toxicity beta‐emitting isotope of hydrogen. Tritium has received international attention because of public and scientific concerns over its release to the environment and the potential health impact of its internalization. This article provides a brief summary of the current state of knowledge of both the biological and regulatory aspects of tritium exposure; it also explores the gaps in this knowledge and provides recommendations on the best ways forward for improving our understanding of the health effects of low‐level exposure to it. Linking health effects specifically to tritium exposure is challenging in epidemiological studies due to high uncertainty in tritium dosimetry and often suboptimal cohort sizes. We therefore argued that limits for tritium in drinking water should be based on evidence derived from controlled in vivo animal tritium toxicity studies that use realistically low levels of tritium. This article presents one such mouse study, undertaken within an international collaboration, and discusses the implications of its main findings, such as the similarity of the biokinetics of tritiated water (HTO) and organically bound tritium (OBT) and the higher biological effectiveness of OBT. This discussion is consistent with the position expressed in this article that in vivo animal tritium toxicity studies carried out within large, multi‐partner collaborations allow evaluation of a great variety of health‐related endpoints and essential to the development of international consensus on the regulation of tritium levels in the environment. Environ. Mol. Mutagen. 59:586–594, 2018. © 2018 The Authors Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society